2019
DOI: 10.1021/acs.iecr.9b02448
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study and DEM Numerical Simulation of Dry/Wet Particle Flow Behaviors in a Spouted Bed

Abstract: In this study, wet particle flow behaviors were investigated in a spouted bed using numerical simulations and experiments. Effects of liquid contents and viscosities were investigated. For the experiment, instantaneous particle distribution and particle velocity distributions were explored. Liquid content and viscosity affected flow pattern together. Keeping increasing liquid content and viscosity, the flow pattern displayed flow instabilities, and the gas channel became curved. Numerical simulation results of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 55 publications
3
11
0
Order By: Relevance
“…This is similar with group C particles . Similar results have been extensively reported. , The abovementioned trend is caused by the combined effect of the liquid bridge force and gas–solid drag force . In view of the whole bed, the drag force tends to fluidize the particles, whereas the liquid bridge force is prone to bond the particles together, maintaining the bed in a stable manner.…”
Section: Introductionsupporting
confidence: 90%
See 1 more Smart Citation
“…This is similar with group C particles . Similar results have been extensively reported. , The abovementioned trend is caused by the combined effect of the liquid bridge force and gas–solid drag force . In view of the whole bed, the drag force tends to fluidize the particles, whereas the liquid bridge force is prone to bond the particles together, maintaining the bed in a stable manner.…”
Section: Introductionsupporting
confidence: 90%
“…7,8 The abovementioned trend is caused by the combined effect of the liquid bridge force and gas−solid drag force. 9 In view of the whole bed, the drag force tends to fluidize the particles, whereas the liquid bridge force is prone to bond the particles together, maintaining the bed in a stable manner. Because the liquid bridge force imposes in various directions, it is difficult to perform a force balance analysis to interpret the bed behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, the CFD-DEM approach is implemented to describe gas−solid flow behaviors in a wet-particle fluidized bed. 15 The governing equations of the gas phase are expressed as follows…”
Section: Cfd-dem Approachmentioning
confidence: 99%
“…The results revealed that the double water injection caused more liquid volumes on the particles, leading to an increase in contact duration. Tang et al 15 Most studies about wet-particle systems neglect the particle shape effect and spherical particles are assumed. In practical processes, a majority of the particles are nonspherical.…”
Section: Introductionmentioning
confidence: 99%
“…The second one is computational fluid dynamics coupled with the discrete element method (CFD-DEM), which tracks the solid phase at the particle-scale level and handles particle collision events through a soft-sphere collision model . However, this high-fidelity numerical method requires numerous computational resources for tracking the solid phase, and thus the majority of the available studies have been carried out for small-scale risers of the CFB with a limited particle number. …”
Section: Introductionmentioning
confidence: 99%